Respuesta :

[tex] \huge\boxed{\sf \green{ Given : }}[/tex]

  • [tex] \red{\sf \: The \: Value \: Of \: x \: in \: 1st \: Eqn \: is \: 3 }[/tex]

  • [tex] \orange{ \sf \: The \: Value \: Of \: x \: in \: 1st \: Eqn \: is \: 2}[/tex]

[tex]\red {\underline{ \sf \: Let's \: Solve \: For \: Eqn \: 1 : }}[/tex]

  • [tex] \sf \: f(x) = {2x}^{3} - {5x}^{2} - x [/tex]

  • [tex] \sf \: f(3) = {2(3)}^{3} - {5(3)}^{2} - 3[/tex]

  • [tex] \sf \: f(3) = 2(27) - 5(6) - 3[/tex]

  • [tex] \sf \: f(3) = 54 - 30 - 3[/tex]

  • [tex] \sf \: f(3) = 24 - 3[/tex]

  • [tex] \red{ \sf \: f(3) = 21}[/tex]

_____________________________________

[tex]\orange {\underline{ \sf \: Let's \: Solve \: For \: Eqn \: 2}}[/tex]

  • [tex] \sf \: f(x) = {4x}^{3} + 3x - 5[/tex]

  • [tex] \sf \: f(2) = - 4 {(2)}^{3} + 3(2) - 5[/tex]

  • [tex] \sf \: f(2) = - 4(8) + 6 - 5[/tex]

  • [tex] \sf \: f(2) = - 32 + 6 - 5[/tex]

  • [tex] \sf \: f(2) = - 26 - 5[/tex]

  • [tex] \orange{ \sf f(2) = - 31}[/tex]

____________________________

[Eqn 3]

f(x) = x³ + 3x² + 6x - 11 when x = 5

  • f(x) = x³ + 3x² + 6x - 11

  • f(5) = (5)³ + 3*(5)²+6*(5)-11

  • f(5) = 125 + 3*(25) + 30 - 11

  • f(5) = 125 + 75 + 30 - 11

  • f(5) = 200 + 30 - 11

  • f(5) = 230 - 11

  • f(5) = 219

____________________________

[Eqn 4]

f(x)=x³ - + 12x - 15 when x = 1

  • f( x ) = x³ - x² + 12x - 15

  • f( 1 ) = ( 1 )³ - ( 1 )² + 12( 1 ) - 15

  • f( 1 ) = 1 - 1 + 12 - 15

  • f( 1 ) = 0 + 12 - 15

  • f( 1 ) = -3

____________________________

[Eqn 5]

f(x) = 2x³ + 6x² + 4x + 8 when x = 2

  • f( x ) = 2x³ + 6x² + 4x + 8

  • f( 2 ) = 2( 2 )³ + 6( 2 )² + 4( 2 ) +8

  • f( 2 ) = 2( 8 ) + 6( 4 ) + 8 + 8

  • f( 2 ) = 16 + 24 + 16

  • f( 2 ) = 40 + 16

  • f( 2 ) = 56

[tex] \boxed{\sf \purple{ Hope \: It's \: Helpful!}}[/tex]

Evaluating the polynomial using direct substitution method will give the following :

f(x) = 2x³ - 5x² - x when x = 3

f(3) = 6

f(x) = -4x³ + 3x - 5 when x = 2

f(2) = -31

Substitution

Substitution simply means to put in place of another.  Therefore,

f(x) = 2x³ - 5x² - x when x = 3

f(3) = 2(3)³ - 5(3)² - 3

f(3) = 2(27) - 5(9) - 3

f(3) = 54 - 45 - 3

f(3) = 6

f(x) = -4x³ + 3x - 5 when x = 2

f(2) = -4(2)³ + 3(2) - 5

f(2) = -4(8) + 6 - 5

f(2) = -32 + 6 - 5

f(2) = -32 + 1

f(2) = -31

learn more on substitution here: https://brainly.com/question/15200459

ACCESS MORE